The Organizational Trap-Gap Framework: A conceptual view of library dysfunction. (March 2020) - Acadia, Spencer
This article offers a conceptual framework of library dysfunction by defining it in terms of 'trap-gaps' that happen when libraries become stuck relying on their outdated, legacy habits that, in turn, lead to discontinuities in new organizational knowledge, competency, and strategy. According to the Organizational Trap-Gap Framework, library leaders may address trap-gaps by blending theories and methods from knowledge management, organizational learning, organizational behavior, and organizational development; supporting a new culture of learning that relies on the socially interactive and performative elements of play, questioning, and imagination; and applying new, reformed processes of knowing, competence, and strategizing. The article concludes with a hypothetical consideration of the trap-gap framework using lack of organizational communication as an example along with further reflection on pertinent issues related to library leaders' utility of the framework such as top-down dynamics, ethics, and cultural environment.